HLA-A02 restricted T-cell cross-reactivity to a microbial antigen - Alar Aints; Marina Šunina; Raivo Uibo (Journal of Immunotoxicology)
Molecular mimicry has been proposed to be a possible mechanism of induction of autoimmunity. In some cases, it is believed that such events could lead to a disease such as Type 1 diabetes (T1D). One of the primary MHC-I epitopes in the non-obese diabetic (NOD) mouse model of T1D has been identified as a peptide from the islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP) protein. In humans, the most common MHC-I model allele is HLA-A02; based on this, the study here identified a potential HLA-A0201-restricted human IGRP epitope as YLKTNLFLFL and also found a homologous A0201-restricted peptide in an Enterococcal protein. Using cells obtained from healthy human donors, it was seen that after a 2-week incubation with the synthetic bacterial protein, healthy A0201+ donor CD8+ cells displayed increased staining for human IGRP-peptide-dextramer. On the other hand, in control cultures, no significant levels of dextramer-staining CD8+ T-cells were detectable. From these outcomes, it is possible to conclude that certain bacterial proteins may initiate CD8+ T-cell-mediated immune reaction toward homologous human antigens.